2023
DOI: 10.1186/s12936-023-04644-w
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic efficacy of artesunate–amodiaquine and artemether–lumefantrine for the treatment of uncomplicated falciparum malaria in Chad: clinical and genetic surveillance

Mahamat Souleymane Issa,
Marian Warsame,
Moussa Hassane Taisso Mahamat
et al.

Abstract: Background Artesunate–amodiaquine (AS–AQ) and artemether–lumefantrine (AL) are the currently recommended first-and second-line therapies for uncomplicated Plasmodium falciparum infections in Chad. This study assessed the efficacy of these artemisinin-based combinations, proportion of day 3 positive patients, proportions of molecular markers associated with P. falciparum resistance to anti-malarial drugs and variable performance of HRP2-based malaria rapid diagnostic tests (RDTs). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 52 publications
(50 reference statements)
0
3
0
Order By: Relevance
“…However, the frequency of deletions detected (41.53% pfhrp2 deletion, 52.72% pfhrp3 deletion) in this study is higher than the reported in previous studies in Nigeria [9,10,17] and in its border countries, such as Chad (12.3% pfhrp2 deletion) [23], Cameroon (1.5% pfhrp2 deletion) [24] and Benin (0% pfhrp2 deletion) [10]. That could be explained by different factors.…”
Section: Discussioncontrasting
confidence: 80%
“…However, the frequency of deletions detected (41.53% pfhrp2 deletion, 52.72% pfhrp3 deletion) in this study is higher than the reported in previous studies in Nigeria [9,10,17] and in its border countries, such as Chad (12.3% pfhrp2 deletion) [23], Cameroon (1.5% pfhrp2 deletion) [24] and Benin (0% pfhrp2 deletion) [10]. That could be explained by different factors.…”
Section: Discussioncontrasting
confidence: 80%
“…For the Pfmdr-1 gene, the single 184F mutation, which has no clear impact on ACT drug efficacy, was highly prevalent in Togo (75.9%). This is usually reported in many African settings such as Ghana [ 65 ], Uganda [ 66 ], Madagascar [ 67 ], Tanzania [ 68 ], and Equatorial Guinea [ 69 ], Chad [ 44 ],…”
Section: Discussionmentioning
confidence: 99%
“…As previously described [ 44 ], multiplex nested PCR assays with indexed primers with unique sample-specific tags (barcodes of individual 8-base indices) specific to the sample and adapter sequences (14 or 15 bases), which enabled the final PCR product to bind to the sequencing flow cell, were used to generated amplicons of targeted sequences were produced. To increase the sample volume and reduce the amount of sample for subsequent protocol steps, 4 µL of PCR reactions for each sample was pooled (96 samples).…”
Section: Recruitmentmentioning
confidence: 99%
“…The eluted DNA was then quantified by fluorometric quantification (Qubit, Thermo Fisher), adjusted to 20 ng/μL and stored at − 20 °C until further use. Amplicons from the target regions (exon 2 of the hrp2 and hrp3 genes) were generated using multiplexed nested PCR assays with indexed primers containing specific tags (barcodes)[ 29 31 ]. A total of 4 μL of PCR reactions from each sample were pooled (96 samples) to increase the sample volume and to minimize the use of samples for the downstream steps of the protocol.…”
Section: Methodsmentioning
confidence: 99%